Advances in desalination technology. (4th May 2005) - Pankratz, Tom M.
Seawater desalination has been the cornerstone of the Middle East's water supply strategy since the mid-1950s, and most of the installed desalination capacity is still provided by multistage flash evaporators. But, desalination is changing. In fact, the term "desalination" is no longer limited to seawater applications; desalination technologies are now routinely employed to desalinate brackish groundwater and repurify municipal effluents. Recent advances in desalination technology have simultaneously reduced costs while dramatically improving performance and reliability to the point where desalination technologies now compete with "conventional" treatment processes in many applications. New commercial strategies and a realisation of the economies-of-scale have led to further improvements in plant economics, and an increase in the size of plants now being developed and constructed. This presentation reviews advances in membrane and membrane pretreatment systems, energy recovery devices, materials of construction, hybrid process configurations, increased unit capacities, and the use of public-private partnerships; all of which have led to reduced capital and operating costs, enabling desalination to be economically competitive with traditional treatment options. Advances in desalination technology have resulted in better performances, lower capital and operating costs, and increased application of desalination systems. In the face of increased water shortages and growing costs of "conventional treatment", this trend will certainly continue.